Twenty years, eight legs, one concept: Describing spider biodiversity in Zootaxa (Arachnida: Araneae) - Jäger, Peter (2021)
Zootaxa published more than a thousand papers on Araneae from 2002 to the present, including descriptions of 3,833 new spider species and 177 new genera. Here we summarise the key contributions of Zootaxa to our current knowledge of global spider diversity. We provide a historical account of the researchers that have actively participated as editors, and recognize the more than 1,000 reviewers without whom none of this would have been possible. We conduct a simple analysis of the contributions by authors and geographic region, which allows us to uncover some of the underlying trends in current spider taxonomy. In addition, we examine some of the milestones in twenty years of spider systematic research in Zootaxa. Finally, we discuss future prospects of spider taxonomy and the role that Zootaxa and its younger sister journal Megataxa will play in it. We would like to dedicate this contribution to the memory of Norman I. Platnick, a crucial figure in the advancement of spider systematics.